Exploiting sp2‐Hybridisation in the Development of Potent 1, 5‐α‐l‐Arabinanase Inhibitors. (20th April 2017) - Coyle, Travis; Debowski, Aleksandra W.; Varrot, Annabelle; Stubbs, Keith A.
Abstract: The synthesis of potent inhibitors of GH93 arabinanases as well as a synthesis of a chromogenic substrate to measure GH93 arabinanase activity are described. An insight into the reasons behind the potency of the inhibitors was gained through X‐ray crystallographic analysis of the arabinanase Arb93A from Fusarium graminearum . These compounds lay a foundation for future inhibitor development as well as for the use of the chromogenic substrate in biochemical studies of GH93 arabinanases. Abstract : Utilising shape in the design of inhibitors of glycosidases : The development of tools to study GH93 arabinanases, important enzymes in the biofuel production and livestock industries, as well as a synthesis of a chromogenic substrate to measure GH93 arabinanase activity are described.